Биологическая активность видов семейства Ericaceae флоры Сибири и Дальнего Востока - Саратиков А. С.; Ахмеджанов Р. Р. Рафик Равильевич; Березовская Р. Р.; Юсубов М. С. Мехман Сулейман-оглы (Сулейманович); Дмитрук М. С.; Басова Е. В. (2006, 2006)
Заглавие с экрана